Effectiveness of evidence-based nursing interventions in the management of patients with schizophrenia - Wen, Jiao; Li, Ming-Yan; Song, Pan-Pan; Teng, Fei (Frontiers in Psychiatry, 2025)
BackgroundSchizophrenia is a severe psychiatric disorder characterized by persistent symptoms, functional impairment, and a high risk of relapse. Evidence-based nursing (EBN) is a patient-centered approach that applies clinical research to improve treatment adherence, reduce symptom severity, and support recovery. This study aimed to evaluate the effectiveness of EBN interventions in improving clinical and functional outcomes in patients with schizophrenia.Material and methodsThis retrospective study, conducted from January 2021 to December 2023, included 156 patients diagnosed with schizophrenia based on DSM-5 or ICD-10 criteria. Patients were divided into an observation group (n = 80) receiving EBN interventions and a control group (n = 76) receiving standard nursing care. EBN protocols included psychoeducation, behavioral rehabilitation, social skills training, family support, and medication supervision. Outcome measures included the Social Disability Screening Schedule (SDSS), Brief Psychiatric Rating Scale (BPRS), Modified Rehabilitation Status Scale (MRSS), and medication adherence rates. Statistical analyses were performed using SPSS 27.0, with a p-value of <0.05 indicating significance.ResultsBaseline characteristics were comparable between groups. After intervention, the observation group demonstrated significant improvements in SDSS and BPRS scores compared to the control group, reflecting enhanced social functionality and symptom management (p < 0.001). MRSS indicators, including dependency, social function, activity ability, and symptom behavior, also showed greater improvements in the observation group (p < 0.001). Medication adherence was significantly higher in the observation group, with higher complete adherence rates (40.0% vs. 19.7%) and fewer cases of non-adherence (25.0% vs. 47.4%, p = 0.003).ConclusionsEvidence-based nursing interventions improve social functionality, symptom management, recovery states, and medication adherence in schizophrenia, emphasizing their value in optimizing clinical outcomes.